STUDENT VOICE LESSONS IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2012)
The dialogue in the classroom are essential in the teaching and learning to ensure that students have a voice in the classroom, the teacher needs to understand that the students get to school, brings with it many opportunities and experiences in dealing with these teacher experiences should be careful to select them for these carry multiple values, discourses and subjectivities. However, we still see that the teacher / student relationship is centered on the teacher which is considered the center of learning, students have no right to talk in class, to express their opinions to be part of the construction of knowledge. Given this, this research aims to verify the dialogue between student and teacher in physical education classes in public school. The work was guided by one central question: Why dialogue is not present in physical education classes? (Methodology) In order to answer this question, we based on a survey of qualitative approach, with which we subsidize the observation of physical education classes with students of 2nd year (high school) in a public school, but also conducted a survey literature, in which collected and analyzed references (books and articles) about the voice of the student. (Conclusion) We conclude that the dialogue is very important during the process of teaching and learning because the classes that will actually take place there must be knowledge exchange. Thus, the search brought contributions to our training process, therefore, allowed us to understand the importance of having a different view in relation to the main subject of our educational practice: the student
Keywords: Dialogue; Physical Education; School